HK DISTRIBUTION MODEL FOR ATMOSPHERIC TURBULENCE CHANNEL UNDER THE INFLUENCE OF POINTING ERRORS - Smilić, Marko; Panić, Stefan; Savić, Milan; Spalević, Petar; Milić, Dejan (Bulletin of Natural Sciences Research, 2016)
In this paper, HK statistical model is considered. The application of HK distribution in modeling atmospheric turbulence channel under the influence of strong and weak turbulences and all irradiance fluctuations are discussed. Expression for atmospherics turbulence channel model, pointing error models and path loss are given. Probability density functions (PDF) for both pointing error models (zero boresight and nonzero boresight) are calculated and graphically represented. Also, average bit-error-rate (BER) for zero boresight pointing error and nonzero boresight pointing error are calculated and graphically represented. Closed form expression for PDF and BER are given. Impact of zero boresight pointing error and nonzero boresight pointing error on transmission over atmospheric turbulence channel in FSO system is explained.